2012
DOI: 10.1007/s10072-012-1122-x
|View full text |Cite
|
Sign up to set email alerts
|

An unusual case of neuro-Behçet’s disease presenting with co-occurence of cerebral venous sinus thrombosis with basilar artery occlusion

Abstract: Non-parenchymal neuro-Behçet disease generally affects cerebral venous sinuses, whereas intracranial intracerebral arterial involvement has been rarely reported. But co-involvement of both intracranial intracerebral artery and venous vascular systems in a patient at the same time has not been mentioned before. To the best of our knowledge, this case involving a 25-year-old male with a 7-year history of Behçet disease is the first reported of this type of involvement. He developed occlusion of the basilar arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…[2,9,[11][12][13][14][15][16][17]20,30,[34][35][36][37][38][39][40] Moreover, warfarin and acetyl salicylic acid have been given to some CVT patients with BD. [10][11][12]17,26,34 Wechsler et al 14 reported that treatment of CVT during acute phase consisted of combined heparin and steroids in 19 patients, steroids alone in three, and heparin alone in three others.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[2,9,[11][12][13][14][15][16][17]20,30,[34][35][36][37][38][39][40] Moreover, warfarin and acetyl salicylic acid have been given to some CVT patients with BD. [10][11][12]17,26,34 Wechsler et al 14 reported that treatment of CVT during acute phase consisted of combined heparin and steroids in 19 patients, steroids alone in three, and heparin alone in three others.…”
Section: Resultsmentioning
confidence: 99%
“…35 Colchium, prednisolone, azathioprine, cyclosporine, and cyclophosphamide have been administered to prevent the recurrence of CVT in BD. 2,9,15,17,[26][27][28]30,[36][37][38][39][40][41][42] Acetazolamide and lumboperitoneal shunts have been installed to reduce intracranial hypertension in some CVT patients with BD. 20,25 We administered colchium, azathioprine, and/or prednisolone to our patients to prevent recurrence and we have not observed any recurrence during follow-up in CVT patients with BD.…”
Section: Resultsmentioning
confidence: 99%
“…Cyclophosphamide is a milestone in the treatment of autoimmune diseases and several case reports found that it might be useful in the prevention of recurrent thrombotic events in these patients. [154][155][156][157][158]…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…İntraserebral hemorajinin nedeninin vasküler yapılardaki inflamasyona bağlı olabileceği öne sürülmektedir. 21 Behçet hastalığında çok nadir de olsa, SAK, intraparankimal hemoraji ve iskeminin aynı hastada ortaya çıkabileceği göz önünde bulundurulmalıdır.…”
Section: Subaraknoid Kanama İntraparankimal Hemoraji Ve Serebral İnfunclassified